Solution to error source model selection problem in IS EASECC - Vladimir M Deundyak; Maria A. Zhdanova; Nadezhda S. Mogilevskaya (Advanced Engineering Research, 2017)
Introduction. The development of error-correcting techniques in digital transmission channels is considered. This is a multiparameter problem the solution of which through the analytical methods is rather difficult. This problem is solved within the framework of an information system for evaluating the applicability of noise-immune coding schemes based on an error sequence obtained from a real communication channel. The work objective is to develop methods for selecting the means of noise-immune protection in the data transmission systems. The key problem is to modify an information system evaluating the applicability of error-correcting coding so that it can choose the most appropriate error-source model for the error flow registered in the particular channel, and coordinate error-correcting codec parameters and characteristics of the communication channel based on the simulation experiments. Note that the choice of error-correcting methods involves selecting not only an algebraic code, but also algorithms for its coding and decoding. The results of using the error-correcting methods depend on the intensity and structure of the errors acting in the transmission channel. Materials and Methods. The basis of the described information system is a specialized software package based on the noise-immune communication channels simulation. To construct such a modification, we suggest adding a new module responsible for the error-source model selection. The module involves a special algorithm for the adequate error-source model selection constructed on the basis of the hidden semi-Markov models theory methods, particularly, on the evaluation problem solution. Research Results. The result of the work is a built-in modification of the information system for assessing the applicability of noise-immune coding schemes which allows, in an automatic mode, selecting a suitable method for a particular data transmission system from a list of the available methods of the anti-jamming protection. Discussion and Conclusions . The results obtained can be applied under designing digital transmission channels. The constructed information system allows for the automation of the process of selecting algorithmic methods of the noise-proof protection in the data transmission systems.